Online Capital Expenditure (CAPEX) and Budget Monitoring System for Supply and Distribution Department (SDD) of Petronas Dagangan Berhad (PDB) - Mohd Amir, Aznim Nadzrah (Universiti Teknologi Petronas, 2006)
The purpose of this report is to present the progress report of the final year project, Online Capital Expenditure (CAPEX) and Budget Monitoring System and to detailed out the requirement for and to review, compare and analyze the study and work of other system that already exist in the market. The focus is more on the enhancement to be integrated to the current system and how the new mechanism is to be implemented. CAPEX is one of the processes in the budget life cycle. The information on CAPEX is useful for managers in order for them to make the right decision at the right time. If we look at the definition of CAPEX, it is a fund spent for the acquisition of a long-term asset. If we look at the investment context and perspective, CAPEX is defined as funds used by a company to acquire or upgrade physical assets such as property, industrial buildings, or equipment. The system is going to be developed for Supply and Distribution Department (SDD) and the focus is going on SDD long term assets. They acquire budget in order to run a project and buy a new equipment or machinery for the depot. There is a lot of process has to be taken into place in order to acquire the budget especially when we are talking about the manual system. All this kind of information need to be maintain as to monitor the performance of the company whether they create value for the business or not. Scope of study includes e-business, database management, software engineering, and system analysis and design.